2008
DOI: 10.1177/0731684407085728
|View full text |Cite
|
Sign up to set email alerts
|

A Taguchi Approach for Investigation of Erosion of Glass Fiber — Polyester Composites

Abstract: Polyester composites reinforced with three different weight fractions of woven E-glass fiber reinforcement are developed. To study the effect of various operational and material parameters on erosive wear behavior of these composites in an interacting environment, erosion test are carried out. For this purpose, an air jet type erosion test rig and the design of experiments approach utilizing Taguchi's orthogonal arrays are used. The findings of the experiments indicate that erodent size, fiber loading, impinge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…Exhaustive literature review on erosion behavior of polymer composites reveal that parameters namely; impact velocity, impingement angle, fiber loading, filler content, erodent size etc. largely influence the erosion rate of polymer composites (Patnaik et al 2008a(Patnaik et al , 2008b(Patnaik et al , 2008c(Patnaik et al , 2008dMahapatra, 2008;Patnaik et al, 2007;Aglan and Chenock, 1993;Harsha et al, 2003;Tamer and Taskiran, 2007;Tewari et al, 2002;Zhou et al, 2005;Rattan and Bijwe, 2007). In the present work, the impact of four such parameters are studied using L9 (3 4 ) orthogonal design.…”
Section: Taguchi Experimental Designmentioning
confidence: 95%
“…Exhaustive literature review on erosion behavior of polymer composites reveal that parameters namely; impact velocity, impingement angle, fiber loading, filler content, erodent size etc. largely influence the erosion rate of polymer composites (Patnaik et al 2008a(Patnaik et al , 2008b(Patnaik et al , 2008c(Patnaik et al , 2008dMahapatra, 2008;Patnaik et al, 2007;Aglan and Chenock, 1993;Harsha et al, 2003;Tamer and Taskiran, 2007;Tewari et al, 2002;Zhou et al, 2005;Rattan and Bijwe, 2007). In the present work, the impact of four such parameters are studied using L9 (3 4 ) orthogonal design.…”
Section: Taguchi Experimental Designmentioning
confidence: 95%
“…Thus, the erosion behaviour of a wide range of fibre-reinforced polymer composites with different matrix materials has recently been evaluated. These include glass and carbon fibre reinforced epoxy [3][4][5], polyester [6][7][8][9], polyetheretherketone (PEEK) [10], polyetherimine (PEI) [11,12] and polyphenylenesulphide (PPS) [13], to name a few. Typically, the effect of the reinforcement material, concentration, type and orientation as well as its adhesion to the matrix has been studied in these investigations.…”
Section: Introductionmentioning
confidence: 99%
“…The Taguchi techniques used to design the experiment on weight loss and friction coefficient prediction models for polyamide‐6 composites filler with 0, 5, and 10 wt% wollastonite (W) particles with different parameters of sliding speed, applied load, and filler ratio . In addition, the analysis of variance (ANOVA) analysis and S/N ratio are used to obtain wear rate on Glass Fiber Polyester Composites . The L 8 orthogonal array used to design the experiment and influence the process parameters found by ANOVA and Linear regression equation, it is concluded that the addition of load and sliding speed is the most significant factors among the selected parameters …”
Section: Introductionmentioning
confidence: 99%
“…[16] In addition, the analysis of variance (ANOVA) analysis and S/N ratio are used to obtain wear rate on Glass Fiber Polyester Composites. [17] The L 8 orthogonal array used to design the experiment and influence the process parameters found by ANOVA and Linear regression equation, it is concluded that the addition of load and sliding speed is the most significant factors among the selected parameters. [18] Design of experiment techniques used for researchers is to minimize the number of experiments and determine significant factor in the selected design levels.…”
Section: Introductionmentioning
confidence: 99%